An Effective Sneak‐Path Solution Based on a Transient‐Relaxation Device. Issue 1 (18th November 2022) - Fu, Tianda; Fu, Shuai; Sun, Lu; Gao, Hongyan; Yao, Jun
Abstract: An efficient strategy for addressing individual devices is required to unveil the full potential of memristors for high‐density memory and computing applications. Existing strategies using two‐terminal selectors that are preferable for compact integration have trade‐offs in reduced generality or functional window. A strategy that applies to broad memristors and maintains their full‐range functional window is proposed. This strategy uses a type of unipolar switch featuring a transient relaxation or retention as the selector. The unidirectional current flow in the switch suppresses the sneak‐path current, whereas the transient‐relaxation window is exploited for bidirectional programming. A unipolar volatile memristor with ultralow switching voltage (e.g., <100 mV), constructed from a protein nanowire dielectric harvested from Geobacter sulfurreducens, is specifically employed as the example switch to highlight the advantages and scalability in the strategy for array integration. Abstract : A strategy in which the transient relaxation in a type of dynamic selector made from unipolar volatile memristors is harnessed to effectively address the sneak‐path problem in memristor arrays is demonstrated.